Does Achievement Motivation Cause Rowers to Burnout? - Bakti, Salma Putri; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
In rowing, athletes face high pressure due to intensive training, intense competition, and expectations from coaches and the environment. Achievement motivation is a significant factor in achieving optimal performance, but excessive pressure can increase the risk of burnout. In the field, many athletes experience physical and emotional exhaustion due to the drive to achieve without good stress management. This study aims to understand the role of achievement motivation, which is generally considered positive but also has the potential to trigger burnout. The method used is quantitative descriptive with an ex-post facto approach, involving active rowing athletes in Bandung City. The research instrument was a closed questionnaire with a scale of achievement motivation and burnout. The results of the study showed a significant relationship between the two. The higher the motivation to celebrate, the lower the risk of burnout, while low motivation increases the risk. In conclusion, a balanced approach is needed in building athlete motivation, by considering psychological factors and training load management. Coaches and support teams are advised to implement burnout prevention strategies, such as optimal recovery programs, psychological assistance, and creating a training environment that supports the mental well-being of athletes.